2022
DOI: 10.1039/d2dt01234k
|View full text |Cite
|
Sign up to set email alerts
|

A multi-technique approach to unveil the redox behaviour and potentiality of homoleptic CuI complexes based on substituted bipyridine ligands in oxygenation reactions

Abstract: The effect of differently substituted 2,2’-bipyridine ligands (i.e. 6,6’-dimethyl-2,2’-bipyridine, 5,5’-dimethyl-2,2’-bipyridine, 6,6’-dimethoxy-2,2’-bipyridine and 2,2’-bipyridine) on the reversible oxidation of the resulting Cu(I) homoleptic complexes is investigated by means of a multitechnique...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 68 publications
1
13
0
Order By: Relevance
“…Test calculations performed on CuBP cis BP trans -Me 2 H 2 , i.e., where one of the two chelating bpy molecules assumes the trans conformation (xyz coordinates of the optimized structure are listed in the Supporting Information, point B8), strongly suggest that this is the same structure that the complexes have in solution: in fact, the latter resulted to be less stable than CuBP-Me 2 H 2 of 31.0 kJ mol −1 . Also, the strong similarities observed between the Raman spectra recorded on dichloromethane solution and on the solid phase of the [Cu(2,2'-6,6′-Me 2 -bpy) 2 ] + [PF 6 ] − complex 5 S1, part b) but also the relative observed changes occurring between the two complexes.…”
Section: ■ Results and Discussionmentioning
confidence: 70%
See 3 more Smart Citations
“…Test calculations performed on CuBP cis BP trans -Me 2 H 2 , i.e., where one of the two chelating bpy molecules assumes the trans conformation (xyz coordinates of the optimized structure are listed in the Supporting Information, point B8), strongly suggest that this is the same structure that the complexes have in solution: in fact, the latter resulted to be less stable than CuBP-Me 2 H 2 of 31.0 kJ mol −1 . Also, the strong similarities observed between the Raman spectra recorded on dichloromethane solution and on the solid phase of the [Cu(2,2'-6,6′-Me 2 -bpy) 2 ] + [PF 6 ] − complex 5 S1, part b) but also the relative observed changes occurring between the two complexes.…”
Section: ■ Results and Discussionmentioning
confidence: 70%
“…All the Cu(I) complexes were synthesized by using the general procedure reported below and previously reported. 5 Synthesis and characterization of [Cu(2,2′-6,6′-Me 2 -bpy) 2 ] + [PF 6 ] − and [Cu-(2,2′-bpy) 2 ] + [PF 6 ] − were previously reported by our group. 5 The NMR spectra were recorded on a Jeol ECZ-R 600 MHz instrument, in deuterated acetone, using the residual solvent peak as an internal reference 1H: 2.05 ppm.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…As part of our work on dinucleating naphthyridine systems, we have revisited the chemistry of 2,7-bis­(2-pyridyl)-1,8-naphthyridine ,, ( H L ) and found that it binds only weakly and reversibly to Zn . Herein, we report the derivative 2,7-bis­(6-methyl-2-pyridyl)-1,8-naphthyridine ( Me L , Figure a), in which the inclusion of 6-Me substituents on the pyridyl groups is envisaged to (i) increase the donor strength, (ii) increase the steric presence proximal to the metal binding site, (iii) improve solubility, and (iv) enhance redox activity of the resulting complexes. In polypyridyl ligand systems, such as 2,2′-bipyridine and 1,10-phenanthroline, substitution adjacent to the nitrogen donors is known to have a significant impact on the redox properties of the system. For example, oxidation and reduction of [Cu­(phen) 2 ] + (phen = 1,10-phenanthroline) are reported to show poor electrochemical reversibility, whereas the 2,9-dimethyl analogue [Cu­(dmphen) 2 ] + (dmphen = 2,9-dimethyl-1,10-phenanthroline) exhibits reversible oxidative and reductive processes involving the Cu I /Cu II redox couple and the dmphen π-system, respectively . The inclusion of 2,9-substituents restricts geometric changes upon oxidation to Cu II , which is manifest in a positive shift in the oxidation potential …”
Section: Introductionmentioning
confidence: 99%